Is platelet-rich plasma better than steroids as epidural drug of choice in lumbar disc disease with radiculopathy? Meta-analysis of randomized controlled trials - Sathish Muthu; Sathish Muthu; Sathish Muthu; Vibhu Krishnan Viswanathan; Vibhu Krishnan Viswanathan; Prakash Gangadaran; Prakash Gangadaran; Prakash Gangadaran (Experimental Biology and Medicine)
The current meta-analysis was performed to analyze the efficacy and safety of platelet-rich plasma (PRP) as an epidural injectate, in comparison with steroids in the management of radiculopathy due to lumbar disc disease (LDD). We conducted independent and duplicate searches of the electronic databases (PubMed, Embase and Cochrane Library) in March 2024 to identify randomized controlled trials (RCTs) analyzing the efficacy of epidural PRP for pain relief in the management of LDD. Animal or in vitro studies, clinical studies without a comparator group, and retrospective or non-randomised clinical studies were excluded. Diverse post-intervention pain scores [visual analog score (VAS)] and functional scores [Oswestry Disability Index (ODI), SF-36], as reported in the reviewed studies, were evaluated. Statistical analysis was performed using STATA 17 software. 5 RCTs including 310 patients (PRP/Steroids = 153/157) were included in the analysis. The included studies compared the efficacy and safety of epidural PRP and steroids at various time-points including 1, 3, 6, 12, 24, and 48 weeks. Epidural PRP injection was found to offer comparable pain relief (VAS; WMD = −0.09, 95% CI [−0.66, 0.47], p = 0.641; I2 = 96.72%, p < 0.001), functional improvement (ODI; WMD = 0.72, 95% CI [-6.81, 8.25], p = 0.524; I2 = 98.73%, p < 0.001), and overall health improvement (SF-36; WMD = 1.01, 95% CI [−1.14, 3.17], p = 0.224; I2 = 0.0%, p = 0.36) as epidural steroid injection (ESI) at all the observed time points in the included studies without any increase in adverse events or complications. Epidural administration of PRP offers comparable benefit as epidural steroid injection (ESI) in the management of radiculopathy due to LDD. The safety profile of the epidural PRP is also similar to ESI.